Pemberdayaan Diri Melalui Terapi Psikoreligius Dalam Mengurangi Kecemasan Jemaah Calon Haji - Moch. Ikwan; Arif Helmi Setiawan; Difran Nobel Bistara (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The Hajj pilgrimage is a complex ritual that often causes anxiety in prospective pilgrims, which can impact mental health and the solemnity of worship. This community service program aims to reduce anxiety levels and empower prospective pilgrims through psychoreligious therapy in order to strengthen their mental and spiritual readiness. This activity uses a participatory approach involving 65 prospective pilgrims from KBIHU Bryan Makkah Surabaya, which is implemented through several stages, namely preparation and permits, socialization and participant recruitment, program implementation and individual mentoring, and evaluation and follow-up. The instrument used is the Zung Self-Rating Anxiety Scale (ZSAS) with pre-test and post-test measurements. The pre-test results showed that the majority of pilgrims were in the moderate (32.31%) and high (44.62%) anxiety categories. After the intervention, there was a significant decrease, with 41.54% of participants being categorized as not anxious, 47.69% in the mild anxiety category, 10.77% in the moderate anxiety category, and no participants were experiencing high anxiety. These findings indicate that strengthening psychological and spiritual aspects reduces anxiety, while broadening its application in the context of mental-spiritual preparation for prospective Hajj pilgrims. Thus, the self-empowerment program through dhikr-based psychoreligious therapy has proven effective in reducing anxiety and is recommended for continued implementation and expansion to other KBIHUs to help more prospective pilgrims prepare for the Hajj with greater calm, confidence, and reverence.